2013
DOI: 10.1038/sc.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of depression on physical complications in spinal cord injury: behavioral mechanisms and health-care implications

Abstract: Study Design: This study is a literature review and a proposed conceptual model. Objectives: The objective of this study is to develop a conceptual model to explore the relationship between the presence of depressive symptoms and secondary physical complications such as pressure ulcers, urinary tract infections and autonomic dysreflexia in spinal cord injury (SCI). Setting: Community setting for individuals with SCI. Methods: A conceptual model explaining the mechanism underlying the relationship between depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 48 publications
(57 reference statements)
0
10
0
2
Order By: Relevance
“…It has been previously concluded that depression can “lead to apathy in terms of self-care” [56]. However, studies also support the idea of “feedback loops” where certain patient factors and increased complications following depression may in turn accentuate the initial depression [57]. Indeed, secondary complications were identified as a barrier to self-management in the current study and thus may be acting as barriers in and of themselves (i.e., decreases in functional capacity) or may be contributing to this described feedback loop.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously concluded that depression can “lead to apathy in terms of self-care” [56]. However, studies also support the idea of “feedback loops” where certain patient factors and increased complications following depression may in turn accentuate the initial depression [57]. Indeed, secondary complications were identified as a barrier to self-management in the current study and thus may be acting as barriers in and of themselves (i.e., decreases in functional capacity) or may be contributing to this described feedback loop.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12][13][14] Cognitive/emotional impairments may be detrimental to SCI patients not only in their own right, but because they can compromise rehabilitation and impair recovery. 15,16 Recent experimental studies have reported that SCI in rodent models causes impairment of spatial and retention memory and depressive-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…recuperação da função sexual através da readaptação à nova condição, bem como a plasticidade das vias nervosas responsáveis pelos comandos autonômicos e função sexual. Além disso, ocorre melhora nos níveis de testosterona e descoberta de outras zonas erógenas que compensam a ausência de sensação genital 23 .…”
Section: Introductionunclassified